Answer
a) g(-8) = 17
b) When g(x) = -7, x = 8
c) When f(x) = g(x), x = (2/3)
d) When f(x) = h(x), x = (1/20)
e) x-intercept of h(x) = (7/16)
Step-by-step explanation
f(x) = 9x - 2
g(x) = 5 - 3x/2
h(x) = 4x - 7/4
(a) Find g(-8).
g(x) = 5 - 3x/2
g(-8) means the value of g(x) when x = -8
g(-8) = 5 - [3×-8/2]
= 5 - (-12)
= 5 + 12
= 17
(b) Find the value of x that makes g(x) = -7.
g(x) = 5 - 3x/2
When g(x) = -7,
5 - 3x/2 = -7
5 - (3x/2) - 5 = -7 - 5
-(3x/2) = -12
![\begin{gathered} (-3x)/(2)=-12 \\ \text{Cross multiply} \\ -3x\text{ = 2}*-12 \\ -3x\text{ = -24} \\ \text{divide both sides by -3} \\ (-3x)/(-3)=(-24)/(-3) \\ x\text{ = 8} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l8vs304k28wv24we2t1yh6ytyx1w4mhukh.png)
(c) Find the value of x that makes f(x) = g(x).
f(x) = 9x - 2
g(x) = 5 - 3x/2
When f(x) = g(x)
9x - 2 = 5 - (3x/2)
9x + (3x/2) = 5 + 2
(21x/2) = 7
![\begin{gathered} (21x)/(2)=7 \\ \text{Cross multiply} \\ 21x\text{ = 2}*7 \\ 21x=14 \\ \text{Divide both sides by 21} \\ (21x)/(21)=(14)/(21) \\ x=(14)/(21)=(2)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/76jy09cz2mpc1oscicof9az7xv5gkkz5jl.png)
(d) Find the value of x that makes f(x) = h(x)
f(x) = 9x - 2
h(x) = 4x - 7/4
When f(x) = h(x)
9x - 2 = 4x - (7/4)
9x - 4x = 2 - (7/4)
5x = (1/4)
![\begin{gathered} 5x=(1)/(4) \\ \text{Divide both sides by 5} \\ (5x)/(5)=(1)/(4*5) \\ x\text{ =}(1)/(20) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fmsefrdp5ueo5oy6aoq1qyddzrlwnuynrc.png)
(e) Find the x-intercept of h(x).
h(x) = 4x - 7/4
The x-intercept is the value of x when h(x) = 0
When h(x) = 0
4x - (7/4) = 0
4x = (7/4)
![\begin{gathered} 4x=(7)/(4) \\ \text{Divide both sides by 4} \\ (4x)/(4)=(7)/(4*4) \\ x=(7)/(16) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/h1ltmnbfe2nzlb5t9o5qwz6vnzlra4lak1.png)
Hope this Helps!!!